1971
DOI: 10.1073/pnas.68.12.3015
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahedral Iron in the Active Center of Plant Ferredoxins and Beef Adrenodoxin

Abstract: The coordination structure of the ironsulfur complex in spinach ferredoxin and adrenodoxin is investigated by optical spectroscopy. The circular-dichroism and absorption spectra of these two-iron iron-sulfur proteins reveal weak electronic transitions in the nearinfrared wavelength range, 0.8-2.5 ,Am (12,500-4000 cm-l).On the basis of the low absorption intensities and large anisotropy factors, d d transitions of the iron can be identified in the reduced proteins at about 4000 cm-' and 6000 cm-. The low energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
0

Year Published

1973
1973
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 22 publications
1
40
0
Order By: Relevance
“…X-ray analysis of the structure of the [Fe-S]2 protein from Spirulina platensis [20] shows that the most likely mode of reaction proceeds via the orbitals of cysteinyl sulfur from residues 39 and 44 which are located on the surface of the molecule. The ferrous iron constituent of the binuclear cluster has tetrahedral symmetry [21,22], but data on the coordination number and symmetry of the ferric component are not available for either oxidized or reduced states• However, there is a report that the ferric sites in oxidized spinach ferredoxin are inequivalent, and the nonreducible site in reduced ferredoxin is proposed to be a highly distorted (squashed toward D2d) tetrahedral structure with the possibility of an additional weak coordination to an available nitrogen or oxygen donor atom [23]. Conceivably, oxygen can distort or partially displace one of the sulfur ligands and form a complex with the iron atom bonded by Cys-39 and Cys-44.…”
Section: Discussionmentioning
confidence: 99%
“…X-ray analysis of the structure of the [Fe-S]2 protein from Spirulina platensis [20] shows that the most likely mode of reaction proceeds via the orbitals of cysteinyl sulfur from residues 39 and 44 which are located on the surface of the molecule. The ferrous iron constituent of the binuclear cluster has tetrahedral symmetry [21,22], but data on the coordination number and symmetry of the ferric component are not available for either oxidized or reduced states• However, there is a report that the ferric sites in oxidized spinach ferredoxin are inequivalent, and the nonreducible site in reduced ferredoxin is proposed to be a highly distorted (squashed toward D2d) tetrahedral structure with the possibility of an additional weak coordination to an available nitrogen or oxygen donor atom [23]. Conceivably, oxygen can distort or partially displace one of the sulfur ligands and form a complex with the iron atom bonded by Cys-39 and Cys-44.…”
Section: Discussionmentioning
confidence: 99%
“…Natural CD spectra (3) Madison, WI. 1 1 In addition to the well-known "390" band, all C2-state proteins exhibit a variably resolved peak at -v9600 cm-' (-u1050 nm); this band has been previously reported (6) (11). In the reduced clusters, the CD (11) shows that electronic transitions exist to well below 5000 cm-1; the lack of observation of MCD here is due to the small magnitude of the MCD anisotropy ratio.…”
mentioning
confidence: 85%
“…These changes in protein conformation may be similar to those which cause changes in the optical absorption and CD when ferredoxin forms a complex with ferredoxin NADP red uctase26 27 Eaton et a!. 28 have investigated the nature of the iron sulphur complex in spinach ferredoxin and adrenodoxin by observing the CD and optical spectra in the near IR wavelength region. They identified d -+ d transitions of the iron atoms in the spectra of the reduced proteins at about 4000 cm and 6000 cm' and from the low energy of these transitions have concluded that the reduced iron-sulphur proteins contain a high spin ferrous ion in a distorted tetrahedral site.…”
Section: Garbett Etmentioning
confidence: 99%